Mineralogical and Geotechnical Characterization of the Clay Layers within the Basal Shear Zone of the 1963 Vajont Landslide - Alberto Bolla; Paolo Paronuzzi; Daniela Pinto; Davide Lenaz; Marco Del Fabbro (Geosciences, 2020)
The 1963 Vajont landslide is a reference example of large rockslides involving clay interbeds emplaced in sedimentary rock masses in correspondence with the basal rupture zone (thinly stratified cherty limestone of the Fonzaso Formation dated to Middle–Upper Jurassic). The basal shear zone of the 1963 Vajont landslide was made up of a chaotic assemblage of displaced rock masses, limestone angular gravel, and spread clay lenses. The mineralogical investigations showed that the clays are characterized by complex assemblages of illite/smectite mixed layers (36–96%) admixed with variable amounts of calcite (4–64%) and quartz (0–6%). The clay layers show highly variable plasticity properties and shear strength characteristics. The samples with a large prevalence of clay mineral content (CM) (CM > 79%) are characterized by low values of the residual friction angle (6.7–14.9°), whereas clay materials characterized by a higher content of granular minerals (calcite and quartz) clearly show greater friction angle values (19.5–26.7°). The high permeability of the limestone angular gravel, which caused a rapid reservoir-induced inflow (1960–1963), together with the low friction angle of the clay layers were responsible for the overall shear strength reduction in correspondence with the basal rupture zone, thus favoring the huge sliding on 9 October 1963.